Numerical Performance Analysis of Terahertz Spectroscopy Using an Ultra-Sensitive Resonance-Based Sensor - Niknam, Sajad; Yazdi, Mehran; Behboudi Amlashi, Salman; Khalily, Mohsen (Frontiers in Physics, 2020)
A terahertz sensor structure is proposed which can sense any variations in the analyte permittivity. The sensor essentially works according to the shifts in the resonance frequencies of its propagated spoof surface plasmonic modes. The proposed structure shows great support for surface plasmon oscillations which is approved by the calculated dispersion diagram. To achieve this, in the terahertz frequencies, a metamaterial structure is presented in the form of a structure with two-dimensional periodic elements. Afterwards, it is shown that the performance of the sensor can be affected by different parameters such as metal stripe thickness, length of metal stripe and width of the metal stripe as the most influential parameters. Each of the mentioned parameters can directly influence on the electric field confinement in the metal structure as well as strength of propagated modes. Therefore, two propagated modes are compared, and the stronger mode is chosen for sensing purpose. The primary results proved that the quality factors of the resonances are substantially dependent on some physical parameters. To illustrate this, a numerical parametric sweep on the thickness of the metal stripe is performed and the output shows that only for some specific dimensions the electromagnetic local field binds strongly with the metal part. In a similar way, a sweeping analysis is run to reveal the outcome for the variation of analyte’s permittivity. In this section, the sensor demonstrates an average sensitivity value, approximately 1550 GHz/Permittivity unit, for a permittivity range between 1 to 2.2, which includes the permittivity of many biological tissues in the terahertz spectrum. Following this, an analysis is presented, in the form of two contour plots, for two electrical parameters; Maximum electric field and maximum surface current based on 24 different paired-values of metal thickness and metal width as two most critical physical parameters. Using the plotted contour diagrams, which are estimated using the bi-harmonic fitting function, the best physical dimension for the maximum capability of the proposed sensor is achieved. As mentioned previously, the proposed sensor can be applied for biological sensing due to its fabrication simplicity and its performance.